Transformative learning experiences in mechanical engineering through mechatronics: From high school to college. Issue 1 (January 2020) - Karkoub, Mansour; Abdulla, Shameel
For many years, educators at all levels have been trying to revamp their teaching styles to optimize the learning process. The availability of new virtual and technical instructional tools has led to significant increase in research in teaching methodologies whose outcome can be split into three categories: (1) lecture delivery, e.g. flipped classroom; (2) interactivity, e.g. instantaneous gathering of students' feedback; and (3) technology in the classroom, e.g. using clickers and other gadgets. The focus of this article is on the latter; particularly, the use of technology in teaching concepts that are hard to grasp by mechanical engineering students. These include electromagnetism, semiconductors, design, controls, and system dynamics. The work presented here is based on data collected from activities with 10th and 11th graders, college sophomores, and seniors. The activities include two-week long Science, Technology, Engineering and Mathematics course and a regular semester long mechanical engineering technical elective. A remarkable level of engagement and participation was observed from the students which led to the successful design and construction of interesting devices and systems which earned them recognition by their colleagues, administrators, and industry visitors. In addition, the student enrollment in the mechanical engineering program has increased by 44% since the start of the Science, Technology, Engineering and Mathematics event for high school students in 2013.